Efektivitas Bahan Penyiraman Leri dan Macam Media Tanam terhadap Pertumbuhan Microgreens Tanaman Bunga Matahari (Helianthus annuus L.) - Rahayu, Fita Dwi; Kusumaningrum, Nora Augustien; Sulistyono, Agus (Universitas Lampung, 2024)
Microgreens are mini vegetable plants with high nutrition that are managed in a controlled growing environment. Management of microgreens requires sufficient water, nutrients, sunlight, planting media and air. The research aims to obtain the nutrient watering materials and media types for sunflower microgreens' growth. This research was carried out in Sumbang Bojonegoro village in October-December 2021. This research was prepared in a Completely Randomized Design (CRD) consisting of 2 factors, namely 2 levels of nutrient watering material, water (P1) and rice-washing water (P2), while 3 levels of planting media: husk charcoal (M1), sand (M2) and cocopeat (M3). The parameters observed were the percentage of germination, germination rate, number of normal and abnormal sprouts, sprout length, cotyledon width, sprout moisture content, sprout wet weight, and sprout dry weight. The observation data was analyzed used analysis of variance (ANOVA), with a further Least Significant Difference (LSD) test is carried out at a test level of 5%. Phytochemical tests for microgreens include chlorophyll, vitamin C and protein levels. The results showed that applying water and rice-washing water were not significantly different in terms of % germination and germination rate, while cocopeat media was more effective in terms of % germination, number of normal sprouts, % water content, wet weight of microgreens, length of sprouts and width of cotyledons. Highest phytochemical content % chlorophyll 23.60 mg/L (water+sand media); % Vitamin C content 59.40 mg/100g (water + husk charcoal media) and % protein content 3.47% (rice-washing water + sand media). Keywords: Planting media, rice-washing water, microgreens, phytochemical, watering